Peningkatan Gizi Ibu Hamil Melalui Edukasi Mengenai Pemenuhan Nutrisi Pada Kelas Ibu Hamil Di Desa Jangur Kabupaten Probolinggo - Wahyudi, Kalvin Edo; Abdullah, Azriel Delmiro Frizzy; Sari, Cindy Kartika; Mustikasari, Indracahyaning; Nurhidayah, Rachmadita; Faj’jrina, Faradila Sofia Nur (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Stunting is a problem of chronic malnutrition due to the provision of food that is not in accordance with the nutritional needs of toddlers. Stunting can occur when fetus is still in the womb and will only be seen after children start turning two years old. Stunting prevention is carried out during the first 1000 days of a child's life. Therefore, counseling on stunting prevention is necessary for pregnant women. The community service activity carried out by the MBKM Thematic KKN Students Group 55 of the East Java "Veteran" Development University is an effort to accelerate towards Stunting-Free Jangur Village and to reduce the incidence of Chronic Energy Deficiency (CED) in pregnant women. The target of this program is pregnant women in Jangur Village. The method used is education through media such as posters, PowerPoint, and educational videos. The stages of this community service activity consist of 2 phases, namely the preparation phase before education and the implementation phase of education. The hope is that the results of the education activity can improve the nutrition of pregnant women in Jangur Village so that the health of the mother and baby during childbirth can be maintained.